An Anti-inflammatory microRNA Signature Distinguishes Group 3 Innate Lymphoid Cells From Natural Killer Cells in Human Decidua - Pelosi, Andrea; Alicata, Claudia; Tumino, Nicola; Ingegnere, Tiziano; Loiacono, Fabrizio; Mingari, Maria Cristina; Moretta, Lorenzo; Vacca, Paola (Frontiers in Immunology, 2020)
Innate lymphoid cells (ILCs) are a heterogeneous subset of lymphocytes deeply implicated in the innate immune responses to different pathogens, in lymphoid organogenesis and in the maintenance of tissue homeostasis. Group 3 innate lymphoid cells (ILC3) have been detected in human decidua, where they play a role in the early inflammatory phase favoring implantation and tissue remodeling as well as in the subsequent regulatory phase preventing fetal rejection and supporting neoangiogenesis. A balance between inflammation and immune tolerance is required to maintain pregnancy, thus maternal immune system must be controlled by finely tuned mechanisms. microRNAs (miRNAs) are small non-coding RNAs with important regulatory roles in immune cells, but their function in decidual ILC3 (dILC3) and in decidual NK (dNK) cells is still undefined. Here, we examined the miRNome by microarray in these cells during the first trimester of pregnancy and compared with miRNA profiles of peripheral blood NK (pbNK) cells from pregnant women. We show that distinct miRNA profiles could clearly distinguish dILC3 from NK cells. Correlation analyses revealed that dNK and pbNK miRNome profiles are more similar to each other as compared to dILC3. In particular, we identified 302 and 279 mature miRNAs differentially expressed in dILC3 as compared to dNK and pbNK, respectively. The expression of miR-574-3p and the miR-99b/let-7e/miR-125a miRNA cluster resulted the most increased in dILC3. Remarkably, gene ontology analysis and pathway enrichments of miRNA targets revealed an involvement of these miRNAs in the promotion of anti-inflammatory responses. In agreement to this finding, we also found a higher expression of the anti-inflammatory miR-146a-5p in dILC3 with respect to NK cells. Overall, our data identified specific miRNA signatures distinguishing dILC3, dNK, and pbNK cells. Our data suggest the existence of a tight epigenetic control mediated by miRNAs in dILC3, potentially acting as a brake to prevent exaggerated inflammatory responses and to maintain the immune homeostasis in the early phases of pregnancy.